Manajemen Sumber Daya Manusia sebagai Instrumen Strategis Penguatan Tata Kelola Kelembagaan Pendidikan Islam - Muchlis Anshori; Rena Nur Fajriyah; Anti Syahrotul Wahidah; Farida Nur Mudmainah Wahyuningsih; Riko Malaya Sandi (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
The dynamics of changes in madrasah management demand the implementation of Islamic education management that is adaptive and oriented towards improving quality. This study aims to analyze the practices of Islamic education management in enhancing the quality of education at MAN 3 Ngawi, as well as to identify key factors that influence the effectiveness of madrasah management. This research uses a qualitative approach with a case study type, conducted directly at MAN 3 Ngawi. Data collection techniques include in-depth interviews, observation, and document study, with main informants being the head of the madrasah, the vice principal, and teachers. The research results indicate several key findings, namely: (1) the implementation of participative and visionary leadership by the head of the madrasah plays an important role in improving both academic and non-academic quality; (2) madrasah program planning that integrates Islamic values with modern management principles can enhance the effectiveness of educational activities; (3) human resource management through professional development of teachers and educational staff contributes to improving the quality of learning; and (4) the continuous implementation of program evaluation and control serves as a supporting factor in maintaining the consistency of madrasah education quality. This study contributes to the study of Islamic education management by providing an empirical overview of the management practices of public madrasahs that are contextual and applicable. Reflectively, the research findings affirm that the improvement of education quality in madrasahs is determined not only by the completeness of the managerial structure but also by the ability of the leaders and all madrasah members to internalize Islamic values into professional and sustainable management practices.